2019
DOI: 10.1186/s12199-019-0827-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of biomass fuel smoke with respiratory symptoms among children under 5 years of age in urban areas: results from Bangladesh Urban Health Survey, 2013

Abstract: BackgroundLittle is known regarding the effect of exposure to biomass fuel smoke inhalation on respiratory symptoms in the Bangladeshi population which is a major health hazard in most of the developing countries. This study aims to explore the association between respiratory symptoms and biomass fuel smoke exposure among children under 5 years of age.MethodsData were extracted from the Bangladesh Urban Health Survey conducted in 2013. A total of 10,575 mothers with at least one surviving children were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
4
21
2
3
Order By: Relevance
“…On the other hand, the finding is lower than a study conducted in Bangladesh which claimed the prevalence of 20.44% [ 29 ]. Similarly, this finding is lower than the prevalence of acute lower respiratory infections among under-five children in 28 sub- Saharan African countries which reported 25.3% [ 30 ].…”
Section: Discussioncontrasting
confidence: 72%
“…On the other hand, the finding is lower than a study conducted in Bangladesh which claimed the prevalence of 20.44% [ 29 ]. Similarly, this finding is lower than the prevalence of acute lower respiratory infections among under-five children in 28 sub- Saharan African countries which reported 25.3% [ 30 ].…”
Section: Discussioncontrasting
confidence: 72%
“…In this study, we have found that the overall prevalence of respiratory symptoms among under-five children was 37.5% at [95% (CI: 34.3-41)], of these (runny nose (25.63%), phlegm (10.48%), and wheezing (9.72 were commonly reported respiratory symptoms. This finding [37.5%] was higher compared with previous studies in Ethiopia [20], India [15,21], Nepal [22], and Bangladesh [17]. The possible explanation could be the variation of the study setting, in which some of the studies were institutional-based, whereas our study was community-based, the study period, and the variability in socio-economic, housing, and environmental inequalities.…”
Section: Discussioncontrasting
confidence: 68%
“…The outcome variable of this study was respiratory symptoms. Respiratory symptoms were defined in this study as to whether the children under-five years of age had been suffering from cough, shortness of breath, wheezing, chest tightness, phlegm, and a problem in the chest including blocked, or running nose [ 17 , 18 ]. Under-five children who have experienced at least one of the above-mentioned symptoms for the last 12 months prior to the study were considered as having respiratory symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Mishra et al [26] found that both biomass cooking fuels and environmental tobacco smoke significantly raised the vulnerabilities of ARI among under-five children. In Bangladesh, the use of in-house biomass fuels increased the risk of respiratory symptoms of children by 18%, after adjusting for residential factors, maternal and child characteristics [33]. Children living in households using solid fuels were 1.19 times more likely to suffer from ARI compared to those living in households using cleaner fuels for cooking in Afghanistan [34].…”
Section: Plos Onementioning
confidence: 99%